Rheumatoid arthritis 1 - Taylor, Peter C. (Henry Stewart Talks, 2020)
Prevalence, heterogeneous presentation, and disease course of rheumatoid arthritis, Classification criteria and radiology, Aetiology and pathophysiology, The role of the immune system and inflammation in rheumatoid arthritis